2023
DOI: 10.1111/mve.12638
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of anopheline mosquitoes from the goat malaria‐endemic areas of Thailand

Abstract: Despite the fact that over a 100 anopheline mosquito species have been identified as human malaria vectors, little is known about ungulate malaria vectors. Consequently, we focused on investigating the bionomics and genetic characterizations of anopheline mosquitoes in goat malaria‐endemic regions. We also attempted to screen for ungulate malaria potential vectors. A total of 1019 female anopheline mosquitoes were collected from six goat farms in four provinces of Thailand from 2020 to 2021. Mosquitoes were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the study, archived mosquito species identified by expert entomologists were used 16 , 49 , 50 . Images were photographed by using two-independent equipment including a camera-adhere mobile phone and a Nikon SMZ745 microscope mounted to a Nikon DS series digital camera (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, archived mosquito species identified by expert entomologists were used 16 , 49 , 50 . Images were photographed by using two-independent equipment including a camera-adhere mobile phone and a Nikon SMZ745 microscope mounted to a Nikon DS series digital camera (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Those archived samples obtained were collected from four-different provinces in Thailand 16 . ( c ) archived mosquito samples obtained from Faculty of Veterinary Science, Chulalongkorn University 49 , 50 , were also captured by both stereomicroscope and mobile phone’s cameras. …”
Section: Methodsmentioning
confidence: 99%